Effects of preconceptional vitamin D levels on in vitro fertilization outcomes in infertile patients with polycystic ovary syndrome: A retrospective cohort study - Tunçcan, Emre; Mohri, Parsa; Dikeç, Mirkan; Karaawi, Fatimah; Kazaz, Elif; Kocatepe, Cavit; Dokuzlu, Gizem; Tıraş, Bülent; Çakıroğlu, Ahmet Yiğit; Korun, Zeynep Ece Utkan (Journal of Obstetrics and Gynaecology Research, 2024)
Background: Vitamin D plays various roles in different stages of reproduction, and abnormalities in its levels are associated with diseases such as polycystic ovary syndrome (PCOS). This study aimed to determine the relationship between initial vitamin D levels and in vitro fertilization (IVF) outcomes in PCOS patients. Methods: This retrospective cohort study included 1174 PCOS patients who consulted the Acıbadem Maslak Hospital IVF Clinic between January 2015 and March 2021. We investigated the effect of preconceptional vitamin D levels on IVF outcomes using data analysis with SigmaPlot 14.5. Results: We found a significant positive correlation between preconceptional vitamin D levels and positive clinical pregnancy rates (p < 0.001) as well as increased endometrial thickness (EMT) on human chorionic gonadotropin (hCG) day (p < 0.001, r = 0.262). The optimal vitamin D cut-off value for predicting positive hCG test results was identified as 13.24 ng/mL, as determined by receiver operating characteristic curve analysis (sensitivity = 0.839, specificity = 0.677). No association was observed with other IVF outcome parameters, miscarriage rates, or clinical pregnancy rates based on EMT. Conclusions: The study suggests that PCOS patients with vitamin D levels above 13.24 ng/mL are more likely to achieve positive hCG results after IVF. These findings highlight the potential importance of vitamin D supplementation in improving pregnancy outcomes for PCOS patients. Additionally, increased EMT on hCG day may explain the higher clinical pregnancy rates associated with elevated vitamin D levels.
CRIS-Team Scopus Importer:2024-11-15
Keywords: endometrial thickness; in vitro fertilization; infertility; polycystic ovary syndrome; vitamin D